Consequences of pressure ulcer among bedridden patient in ATBUTH Bauchi, Bauchi State, Nigeria - Muhammad, Salisu Umar; Maimuna MUHAMMAD; Sanusi Haruna IBRAHIM; Fahad AHMED; Fatima Muhammad DAMBAM (RADINKA JAYA UTAMA PUBLISHER, 2025)
This study explores the extensive consequences of pressure ulcers among bedridden patients. Pressure ulcers, also known as bedsores or pressure sores, pose significant health challenges for individuals with limited mobility. The research investigates the physical, psychological, and economic impacts of pressure ulcers on patients and the healthcare system. Physically, pressure ulcers can cause tissue damage and infections due to prolonged pressure on specific areas, leading to skin deterioration. Psychologically, patients suffering from pressure ulcers may experience pain, discomfort, anxiety, depression, and a reduced quality of life. Economically, managing pressure ulcers incurs substantial treatment costs, including specialized wound care products and frequent medical consultations. This study highlights the burden placed on healthcare systems and caregivers due to the demanding care required for the prevention and treatment of pressure ulcers. Pressure ulcers are a prevalent and debilitating complication among bedridden patients, leading to significant morbidity, mortality, and healthcare costs. This study investigates the consequences of pressure ulcers on bedridden patients, identifies risk factors associated with their development, and explores demographic factors that increase their risk. Our findings indicate that pressure ulcers significantly impact patients' physical and psychological well-being, healthcare utilization, and quality of life. We identified key risk factors, including immobility, sensory impairment, poor nutrition, and inadequate care practices. Additionally, our analysis reveals significant demographic associations, with older adults, females, and those with comorbid diseases being more susceptible. This study highlights the urgent need for proactive prevention strategies, timely detection, and effective management to mitigate the consequences of pressure ulcers and improve patient outcomes.